OS DESAFIOS E AS BARREIRAS DAS PESSOAS COM DEFICIÊNCIA FÍSICA ADQUIRIDA - PAULO, Ana Beatriz; ANDRADE, Antônio Carlos; CAMARGO, Alex; GRUBERT, Sarah; LIMA, Valéria Regina; SILVA, Vilson; AGUIAR, Wander (ANAIS DO ENIC, 2025)
.